If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -25x + 60 = 0 Reorder the terms: 60 + -25x + 5y = 0 Solving 60 + -25x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -25x + -60 + 5y = 0 + -60 Reorder the terms: 60 + -60 + -25x + 5y = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -25x + 5y = 0 + -60 -25x + 5y = 0 + -60 Combine like terms: 0 + -60 = -60 -25x + 5y = -60 Add '-5y' to each side of the equation. -25x + 5y + -5y = -60 + -5y Combine like terms: 5y + -5y = 0 -25x + 0 = -60 + -5y -25x = -60 + -5y Divide each side by '-25'. x = 2.4 + 0.2y Simplifying x = 2.4 + 0.2y
| x+34=34 | | 4y-24x+20=0 | | 23x*234=456x+56 | | 1+(-6)= | | 9+(-9)= | | 40+34x=235x+90 | | (-2)+(-7)= | | -15+4x=1 | | 3a-1=53 | | 2x+8=28 | | 2x+7=0 | | 4x=3(21-x) | | 59+32x=74-2x | | 45-90+x=90 | | 10X+11y=11 | | 1x-5=10 | | 23x+78=x | | 30x+90=90 | | 14V+5-5V=4(V+5) | | C+5=26-2C | | (2sin^2x)+(3sinx)+1=0 | | 3z=45 | | 8n+3=6n+9 | | x+(x+50)+y=180 | | 23w=x-fg-we | | 23w=x | | 2x-10=x | | 4(x)+9= | | 3(8t+13)=303 | | 9x+8+7x=34+3x | | x^6+2x^3-3=0 | | 234=x |